2020
DOI: 10.1111/jch.13963
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of laparoscopic‐based renal denervation plus adrenalectomy vs adrenalectomy alone for treating resistant hypertension caused by unilateral aldosterone‐producing adenoma

Abstract: Previous studies describing renal denervation (RDN) from the intima of the renal artery for the treatment of resistant hypertension have reported variable efficacies, and RDN triggers renal intimal injury and atherosclerosis. This study aimed to evaluate the efficacy and safety of RDN from the adventitia of renal artery plus unilateral laparoscopic adrenalectomy to treat patients with resistant hypertension caused by unilateral aldosterone-producing adenoma (APA). A total of 60 consecutive patients with resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…From the results of previous studies, the ambulatory BP and office BP of the RDN group decreased more significantly than those of the control group, and combined laparoscopic adrenalectomy with adventitia‐RDN was equally safe at one year postprocedure. 16 This report also carried out a 3‐year long‐term follow‐up of the clinical study. From the results of our study, it can be seen that both laparoscopic adrenalectomy on the affected side alone and laparoscopic adrenalectomy combined with adventitia‐RDN can safely and effectively reduce BP in patients with resistant hypertension caused by APA.…”
Section: Discussionmentioning
confidence: 98%
“…From the results of previous studies, the ambulatory BP and office BP of the RDN group decreased more significantly than those of the control group, and combined laparoscopic adrenalectomy with adventitia‐RDN was equally safe at one year postprocedure. 16 This report also carried out a 3‐year long‐term follow‐up of the clinical study. From the results of our study, it can be seen that both laparoscopic adrenalectomy on the affected side alone and laparoscopic adrenalectomy combined with adventitia‐RDN can safely and effectively reduce BP in patients with resistant hypertension caused by APA.…”
Section: Discussionmentioning
confidence: 98%
“…Although there are currently no published RDN registries in Chinese mainland, two RDN clinical trials have been conducted. RDN was performed using a saline-irrigated ablation catheter in one of the trials, [57] and by adventitia ablation using a radiofrequency catheter following laparoscopic adrenalectomy in the other trial [58] . Although no sham-controlled groups were included, both randomized trials demonstrated the efficacy of RDN in reducing office and ambulatory BP for up to 12 months.…”
Section: Rationale and Clinical Evidence For Rdnmentioning
confidence: 99%
“…If the BP is not controlled following definitive treatment for the secondary causes it is reasonable to recommend RDN, since hypertension is inherently a multifactorial disease. [ 58 ] In the ARDeC consensus, patients with suspected higher sympathetic tone, including Asian hypertensive patients, [ 70 ] patients with obstructive sleep apnea, and patients with increased 24-h ambulatory heart rate (>74/min), [ 43 , 71 ] and features of salt sensitivity such as asleep hypertension and morning hypertension [ 59 , 70 ] are considered to be ideal candidates for RDN. The ARDeC consensus also recommends that patients with resistant hypertension, those with established cardiovascular disease, and those who are either intolerant or do not adhere to antihypertensive medications are ideal candidates.…”
Section: Consensus Documents On Rdn Worldwidementioning
confidence: 99%
See 1 more Smart Citation
“…Various other modalities, including microwave, [65] ionizing radiation, [66] cryo-ablation [67,68] and modified laparoscopic techniques [69,70] have been studied for RDN application, each with specific potential clinical advantages. However, these technologies have not yet progressed beyond the pre-clinical or early first in man phase of research.…”
Section: Other Energy Modalitiesmentioning
confidence: 99%